Unraveling The Influence of Halal Certification Logos on Consumer Choises: A Meta-Analysis in The Indonesian Market - Syaakir Sofyan; A. Syathir Sofyan; Ishfaq Ahmed; Ega Rusanti; Noval Noval; Nur Syamsu (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
The aim of this research is to examine the development of research on the influence of halal logos on purchasing decisions for halal products in Indonesia. The method used is meta analysis by reviewing 33 studies published in 2013-2023 with the help of the OpenMEE application. The results of this research show that there is a positive influence of the logo on decisions with a p-value obtained <0.001 and an estimated value of 0.415, which indicates that the strength of the relationship is in the medium category. The influence of the halal cosmetics industry is greater than that of the halal food industry. In terms of sample type, the student sample effect is greater than the general public sample effect. Meanwhile, in the location group, the effect of the provincial capital is greater than the effect of location in the district. Theoretically, this study strengthens the Theory of Planned Behavior (TPB) by confirming the role of halal logos as external cues that influence consumer attitudes and intentions. It also highlights the halal logo as a trust signal that shapes purchasing behavior across different contexts. Study limitations include limited sample size and lack of adequate moderators to explain within-subgroup variation. Therefore, future research needs to consider testing other important aspects, such as participant groups, countries/regions, and other variables.